Selection of Literary Readings for Junior High School Students Based on the Horizon of Public Readers' Acceptance of Kompas Selected Short Stories 2024 - Ira Susma Sari; Yusro Edy Nugroho (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Literary learning in junior high school still often chooses short stories based on the reputation of the work or the availability of materials, while the acceptance of students as lay readers has not been used as a basis for selecting texts. This research aims to describe the horizon of student acceptance for the twelve Kompas Selected Short Stories 2024 and formulate criteria for curating junior high school literature readings. This descriptive qualitative research involved 23 students of grade VII C of Sekolah Rakyat Menengah Junior 6 East Jakarta. Data were obtained through written responses about predictions, feelings, understanding, and further desires after reading, as well as learning observations. The data were analyzed heuristically and hermeneutically with the categories of expectation horizon, reception horizon, advanced response, and reception variation. The results showed that short stories with concrete conflicts, relatively clear language, easily recognizable characters, and themes related to students' experiences tended to receive positive responses. Ambivalent or resistive responses arise when the text contains cultural vocabulary, dense symbols, distant socio-political contexts, or sensitive themes. These findings resulted in five curation criteria, namely readability, experiential proximity, clarity of conflict, thematic sensitivity, and reflectivity. Practically, these criteria can be used to classify short stories as priority reading, supervised reading, or selective reading, while determining support such as context introduction, glossary, and directed discussion